Investigating the environmental drivers of deep‐seafloor biodiversity: A case study of peracarid crustacean assemblages in the Northwest Atlantic Ocean - Oliver S. Ashford; Andrew J. Kenny; Christopher R. S. Barrio Froján; Tammy Horton; Alex D. Rogers (Ecology and Evolution, 2019)
Abstract The deep‐sea benthos covers over 90% of seafloor area and hosts a great diversity of species which contribute toward essential ecosystem services. Evidence suggests that deep‐seafloor assemblages are structured predominantly by their physical environment, yet knowledge of assemblage/environment relationships is limited. Here, we utilized a very large dataset of Northwest Atlantic Ocean continental slope peracarid crustacean assemblages as a case study to investigate the environmental drivers of deep‐seafloor macrofaunal biodiversity. We investigated biodiversity from a phylogenetic, functional, and taxonomic perspective, and found that a wide variety of environmental drivers, including food availability, physical disturbance (bottom trawling), current speed, sediment characteristics, topographic heterogeneity, and temperature (in order of relative importance), significantly influenced peracarid biodiversity. We also found deep‐water peracarid assemblages to vary seasonally and interannually. Contrary to prevailing theory on the drivers of deep‐seafloor diversity, we found high topographic heterogeneity (at the hundreds to thousands of meter scale) to negatively influence assemblage diversity, while broadscale sediment characteristics (i.e., percent sand content) were found to influence assemblages more than sediment particle‐size diversity. However, our results support other paradigms of deep‐seafloor biodiversity, including that assemblages may vary inter‐ and intra‐annually, and how assemblages respond to changes in current speed. We found that bottom trawling negatively affects the evenness and diversity of deep‐sea soft‐sediment peracarid assemblages, but that predicted changes in ocean temperature as a result of climate change may not strongly influence continental slope biodiversity over human timescales, although it may alter deep‐sea community biomass. Finally, we emphasize the value of analyzing multiple metrics of biodiversity and call for researchers to consider an expanded definition of biodiversity in future investigations of deep‐ocean life.